SISTEM PENDETEKSI KEBOCORAN GAS LPG MENGGUNAKAN METODE REALTIME DATABASE PADA SISTEM RTOS (REAL TIME OPERATING SYSTEM) DENGAN LAYANAN FOG - CLOUD COMPUTING - Ipung Saputra; Makhsun Makhsun; Murni Handayani (Jurnal Ilmiah Global Education, 2023)
LPG gas leaks cause serious problems in its use, it is very vulnerable to leaks that cause LPG gas cylinders to explode and catch fire, therefore an automatic gas leak detection and monitoring system was developed. If a gas leak occurs, the sensor will immediately recognise the incident and send a notification in the form of an alarm sound and a warning notification sent to the Smartphone. This detection system is made to determine gas leaks in gas cylinder regulators using the Relatime Database method on the RTOS (Real Time Operating System) system with Fog-Cloud Computing services.